Return on Assets as A Mediator: The Effect of Current Rasio and Debt to Equity Ratio on Firm Value - Shidiq Baddruzzaman; Mardiyani; Benny Dhevyanto (Indonesian Journal of Business Analytics, 2026)
Escalating rivalry within the corporate landscape compels enterprises, particularly those in the technological sphere, to perpetually refine and safeguard their organizational worth. Within the Indonesian context, the tech industry serves as a pivotal pillar for bolstering national economic progress and fast-tracking digital transformation. Nevertheless, despite its critical contributions, this sector has witnessed a persistent downturn in equity performance throughout the preceding three-year period. This inquiry investigates how the Current Ratio (CR) and Debt to Equity Ratio (DER) impact corporate value, utilizing Return on Assets (ROA) as an intervening factor. Employing a quantitative framework with a causal-associative blueprint, the study analyzed data via path analysis using LISREL version 10.20 to assess both proximate and distal variable correlations. The population encompasses technology-based entities listed on the Bursa Efek Indonesia from 2022 to 2024. Through purposive sampling, 25 organizations were identified, yielding 75 distinct observations. Empirical evidence indicates that CR exerts no substantial influence on either ROA or market valuation. Conversely, while DER significantly affects ROA, it lacks a direct statistical link to firm value. Findings highlight that ROA markedly determines firm value and functions as an effective bridge between DER and corporate worth, though it fails to facilitate the impact of CR. Consequently, tech-driven businesses should emphasize optimizing asset productivity and profitability—specifically by leveraging intangible resources—to bolster their market standing and secure investor trust.